Osteoid osteoma of the rib: A rare presentation and treatment with surgical segmental excision - Pandey, Suresh (Nepal Orthopaedic Association Journal, 2020)
Osteoid osteoma is one of the rare benign bone tumors occurring commonly in lower limb long bones either in cortex or medulla. It presents with pain typically more at night and relieved with Aspirin and other NSAIDs. Rib is very rare site of occurrence and there are very few case reports of osteoid osteoma of rib in the literature. We present this case report of Osteoid osteoma of rib arising from shaft of left 6th rib because of its rarity which was successfully treated with marginal excision of the rib segment.